PENGARUH BUDAYA ORGANISASI DAN SERIKAT PEKERJA TERHADAP KEPUASAN KERJA KARYAWAN TETAP DI PT. ELITESTAR PRIMAJAYA GRESIK - mubarroq, abdullah; Minallah, Yasin (Fakultas Ekonomi Universitas Gresik, 2018)
The study has three main objectives: firstly, analyzing the influenceof organizational culture on job satisfaction, secondly analyzing theinfluence of the union on job satisfaction, and thirdly analyzing theinfluence of organizational culture and union on employee job satisfaction.Sampling method using Non Probability Sampling technique. The test usedis multiple regression. The results of this study indicate that there ispartially and simultaneous influence on organizational culture variableand union on employee job satisfaction, seen significant value below 0,05and Fcount (33,887) > Ftable (3,10). The result of this research showsthat tcount value on organizational culture variable (3,373) > t table(1,986), it is stated that organizational culture variable has significantinfluence on employee job satisfaction, while t count with t table on unionvariable 4,889 > t table 1.986) then declared union variable there is asignificant influence on employee job satisfaction. In determination testthere is influence of 42% from independent variable (organizationalculture and union) to dependent variable (job satisfaction of permanentemployee). Meanwhile, 58% is influenced by other variables and notincluded in this regression analysis, such as compensation, motivation,performance and others.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3475678